2017
DOI: 10.3906/vet-1606-65
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supplementing diet with microalgae (Schizochytrium limacinum)on growth and metabolism in lambs during the summer

Abstract: This experiment was conducted at a livestock experiment station. All the scientists in the experiment are licensed to perform experiments on animals and the protocol was approved by the Ethics Committee of UÜHADYEK (approval date: 23.05.2014; no: 2014-09/05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Simultaneously, adding Sargassum latifolium resulted in decreasing glucose, total lipids, cholesterol and triglycerides. In agreement with our findings, Kannan et al (2007a, b) and Ekin et al (2017) recorded that blood cholesterol tended to decrease in goats, dairy cows and lambs fed diets containing algae during stress. Sargassum latifolium is rich in sulfated polysaccharides such as fucoidans and alginate (Mohsen et al, 2007;Gamal-Eldeen et al, 2009).…”
Section: Metabolic Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…Simultaneously, adding Sargassum latifolium resulted in decreasing glucose, total lipids, cholesterol and triglycerides. In agreement with our findings, Kannan et al (2007a, b) and Ekin et al (2017) recorded that blood cholesterol tended to decrease in goats, dairy cows and lambs fed diets containing algae during stress. Sargassum latifolium is rich in sulfated polysaccharides such as fucoidans and alginate (Mohsen et al, 2007;Gamal-Eldeen et al, 2009).…”
Section: Metabolic Parameterssupporting
confidence: 93%
“…have been used as useful alternative feed to livestock because they contain sources of valuable foodstuffs such as essential and non-essential amino acids, some vitamins, antioxidant compounds, dyes and polyunsaturated fatty acids, that are beneficial to animal health (CEVA, 2005;Ananthi et al, 2010;Evans and Critchley, 2014). In this respect, Abdoun et al (2014) and Ekin et al (2017) suggested that algae might positively impact metabolism and reduce lipid concentrations in growing lambs. These knowledge about seaweeds will open new avenues for investigations for exploiting potential of this neglected unconventional resource for the feed industry that could play a vital role in sustainable development of the livestock sector.…”
Section: Introductionmentioning
confidence: 99%
“…Narimani-Rad et al (2012) observed that the inclusion of SO at 0, 2.5 or 5% of a forage-based diet did not affect ME, OMD, and net energy of diets. Sucu et al (2017) observed that feeding lambs on diets supplemented with SA at 5 g/d increased ruminal SCFA concentration and decreased rumen pH, without affecting ruminal ammonia-N concentration.…”
Section: Inoculum Additivementioning
confidence: 87%
“…The reported values in Table 5 indicate a normal ruminal fermentation environment for the culture medium. The lower ruminal pH may be related to the increased concentration of ammonia and total SCFA observed with the additive supplementation (Sucu et al, 2017), or due to increased energy density (Morsy et al, 2015) in the diets. The increased total SCFA production and decreased pH reflect a higher extent of fermentation with the inclusion of SO and SA.…”
Section: Inoculum Additivementioning
confidence: 99%
See 1 more Smart Citation